Counsellor Education : A Paradox - Davis, William L.; Marks, Stephen E. (Canadian Journal of Counselling and Psychotherapy, 1972)
This article examines the nature and impact of paradoxical situations in counsellor education. The counsellor educator and trainee are the focus for defining and then examining these dilemmas. The counsellor educator is constantly forced to shift between the role of counsellor and that of educator. He also must resolve the conflict between his personal and professional growth needs and his commitment to a training program. The second area of paradoxes that are examined concern the counsellor trainee. He is confronted with two major dilemmas: first, the conflict between being both a student and a client; and second, the apparent incongruity between wanting information and specific answers which are either not available or unanswerable at his particular stage of development. This is analogous to the development of a tolerance for ambiguity. All these paradoxes contribute to making the process of counsellor education an endeavour that moves well beyond the simple transmission of counselling skills.